2012
DOI: 10.1002/anie.201201374
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(II)‐Catalyzed Cyclization of Bis(N‐tosylhydrazone)s: An Efficient Approach towards Polycyclic Aromatic Compounds

Abstract: Ahead of the PAC: Polycyclic aromatic compounds (PACs) can be easily accessed by the combination of Suzuki–Miyaura cross‐coupling and a [Rh2(OAc)4]‐catalyzed carbene reaction using easily available bis(N‐tosylhydrazone)s as intermediates (see scheme; Ts=4‐toluenesulfonyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 76 publications
3
71
0
1
Order By: Relevance
“…All the cobalt-porphyrin catalysts [Co II ( P1 )], [Co II ( P2 )] [Co II ( P3 )], and N tosylhydrazone sodium salts were synthesized according to published procedures. 7a,8,11 All the alkynes were used as purchased from Aldrich. All other chemicals were purchased from commercial suppliers and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the cobalt-porphyrin catalysts [Co II ( P1 )], [Co II ( P2 )] [Co II ( P3 )], and N tosylhydrazone sodium salts were synthesized according to published procedures. 7a,8,11 All the alkynes were used as purchased from Aldrich. All other chemicals were purchased from commercial suppliers and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…10 The use of N -tosylhydrazones 11 as diazo precursors in [Co(Por)]-based metalloradical catalysis was thus far unprecedented, which may open up a new area to bring about new chemical transformations using in-situ generated unstable diazo-precursors that are otherwise difficult to handle. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Complementary approaches have been developed to overcome these challenges that are based on Diels-Alder cycloaddition reactions, 13 radical cyclizations, 14 and metal-mediated cycloisomerizations. 15 Additionally, rhodium-and ruthenium-catalyzed procedures have been reported that rely on bis(N-tosylhydrazone) 16 2 as substrate (Fig. 1A I) and olefin-metathesis reactions of bis(alkenes) 17 4 (Fig.…”
mentioning
confidence: 99%
“…In his approach bis(N-tosylhydrazone)s were cyclized using an Rh-catalyst [93]. The starting materials are easily accessible via Suzuki cross-coupling reaction (Scheme 37).…”
Section: Transition Metal Mediated Cyclizationsmentioning
confidence: 99%